Osteogenic effects of a physical activity intervention in South African black children - Meiring, R.; Micklesfield, L.; Avidon, I.; McVeigh, Joanne (2014)
Objectives: To determine whether a weight-bearing physical activity intervention improves measures of bone density, size and strength in a pre- and early pubertal cohort of black South African children. Methods: Twenty two school children (9.7±1.1 years) were cluster randomised into an exercise (EX; n=12) and control (CON; n=10) group. EX children performed a weight-bearing exercise program for 20 weeks. CON children continued their regular activities. Whole body DXA and tibial peripheral QCT scans were obtained. Urine was analysed for concentrations of cross-linked N-telopeptides of Type I collagen (NTX).Results: Changes in 4% volumetric BMD, area and strength were greater in EX than CON. At the 38% site, change in bone area and density was greater in EX than CON. The greater change in periosteal circumference in the EX groups also resulted in a greater change in cortical thickness of the tibia compared to the CON group. NTX concentration was lower in the EX group than the CON group after the intervention. Conclusions: This study documents for the first time the beneficial response of trabecular and cortical bone of black children to a weight bearing exercise intervention.